Gender-based predilection for the microbial load of Aggregatibacter actinomycetemcomitans present in anterior versus posterior implant sites: A preliminary observational study - Sengupta, Soumee; Ganesh, S; Meenakshi, S; Rao, Raghavendra; Swamy, K (Journal of dental implants, 2022)
Purpose of Study: Bacterial biofilm-induced peri-implantitis has been one of the leading causes of implant failure. There are a plethora of local and systemic factors that have been studied at a depth and thereafter have been proven to have a contributory role in the overall disease progression. Epidemiological factors such as site specificity and gender stand to be two confounding factors that have insufficiency in the literature regarding their involvement in the same. Thus, the present article aims to address this gap in the literature and present conclusive evidence about the gender-based comparative evaluation of the microbial load of Aggregatibacter actinomycetemcomitans, one of the potential periodontopathogens for the disease progression, present in anterior versus posterior implant sites. Materials and Methods: Twelve patients (six males and six females) undergoing the implant prosthetic rehabilitation at two intraoral sites, one anterior and one posterior region, were selected as suitable subjects and the healing abutments as the clinical test samples. Culture-independent microbiological analysis was carried out for all the samples for quantification of A. actinomycetemcomitans. Results: The mean viable bacterial DNA count was 503076.49 copies/μL for the male subjects and 474587.85 copies/μL for the female subjects. Hence, there was no significant function correlating gender specificity and the viable bacterial DNA counts. The mean total of viable bacterial DNA counts for the anterior region (site 1) was 407087.17 copies/μL and for the posterior region (site 2) was 570577.17 copies/μL, irrespective of the gender. Thus, a highly significant difference was observed in the mean viable bacterial DNA counts between site 1 and site 2 (F = 20.214; P = 0.001) irrespective of the gender. Conclusion: There seems to be no gender-based predilection for the quantification of viable bacterial DNA counts for A. actinomycetemcomitans. However, a propensity for the presence of higher bacterial load of A. actinomycetemcomitans, one of the causative microorganisms of per-implant diseases, does exist for the implants placed in the posterior region as compared to those placed in the anterior region.